#### Answer

$fog(x)=f(g(x))=f(x^2)=x^2-7$
$gof(x)=g(f(x))=g(x-7)=(x-7)^2=x^2-14x+49$
See graph.

#### Work Step by Step

We are given that:
$f(x)=x-7$
$g(x)=x^2$
$fog(x)=f(g(x))=f(x^2)=x^2-7$
$gof(x)=g(f(x))=g(x-7)=(x-7)^2=x^2-14x+49$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$fog(x)=f(g(x))=f(x^2)=x^2-7$
$gof(x)=g(f(x))=g(x-7)=(x-7)^2=x^2-14x+49$
See graph.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.